Post-remission treatment with allogeneic stem cell transplantation in patients aged 60 years and older with acute myeloid leukaemia: a time-dependent analysis. Issue 10 (October 2015) - Versluis, Jurjen; Hazenberg, Carin L E; Passweg, Jakob R; van Putten, Wim L J; Maertens, Johan; Biemond, Bart J; Theobald, Matthias; Graux, Carlos; Kuball, Jurgen; Schouten, Harry C; Pabst, Thomas; Löwenberg, Bob; et al.
Summary: Background: Acute myeloid leukaemia mainly affects elderly people, with a median age at diagnosis of around 70 years. Although about 50–60% of patients enter first complete remission upon intensive induction chemotherapy, relapse remains high and overall outcomes are disappointing. Therefore, effective post-remission therapy is urgently needed. Although often no post-remission therapy is given to elderly patients, it might include chemotherapy or allogeneic haemopoietic stem cell transplantation (HSCT) following reduced-intensity conditioning. We aimed to assess the comparative value of allogeneic HSCT with other approaches, including no post-remission therapy, in patients with acute myeloid leukaemia aged 60 years and older. Methods: For this time-dependent analysis, we used the results from four successive prospective HOVON-SAKK acute myeloid leukaemia trials. Between May 3, 2001, and Feb 5, 2010, a total of 1155 patients aged 60 years and older were entered into these trials, of whom 640 obtained a first complete remission after induction chemotherapy and were included in the analysis. Post-remission therapy consisted of allogeneic HSCT following reduced-intensity conditioning (n=97), gemtuzumab ozogamicin (n=110), chemotherapy (n=44), autologous HSCT (n=23), or no further treatment (n=366). Reduced-intensity conditioning regimens consisted of fludarabine combined with 2 Gy of total body irradiation (n=71), fludarabine with busulfan (n=10), or other regimens (n=16). A time-dependent analysis was done, in which allogeneic HSCT was compared with other types of post-remission therapy. The primary endpoint of the study was 5-year overall survival for all treatment groups, analysed by a time-dependent analysis. Findings: 5-year overall survival was 35% (95% CI 25–44) for patients who received an allogeneic HSCT, 21% (17–26) for those who received no additional post-remission therapy, and 26% (19–33) for patients who received either additional chemotherapy or autologous HSCT. Overall survival at 5 years was strongly affected by the European LeukemiaNET acute myeloid leukaemia risk score, with patients in the favourable risk group (n=65) having better 5-year overall survival (56% [95% CI 43–67]) than those with intermediate-risk (n=131; 23% [19–27]) or adverse-risk (n=444; 13% [8–20]) acute myeloid leukaemia. Multivariable analysis with allogeneic HSCT as a time-dependent variable showed that allogeneic HSCT was associated with better 5-year overall survival (HR 0·71 [95% CI 0·53–0·95], p=0·017) compared with non-allogeneic HSCT post-remission therapies or no post-remission therapy, especially in patients with intermediate-risk (0·82 [0·58–1·15]) or adverse-risk (0.39 [0·21–0·73]) acute myeloid leukaemia. Interpretation: Collectively, the results from these four trials suggest that allogeneic HSCT might be the preferred treatment approach in patients 60 years of age and older with intermediate-risk and adverse-risk acute myeloid leukaemia in first complete remission, but the comparative value should ideally be shown in a prospective randomised study. Funding: None.